2015
DOI: 10.1039/c5cc04721h
|View full text |Cite
|
Sign up to set email alerts
|

A doubly responsive probe for the detection of Cys4-tagged proteins

Abstract: Recombinant proteins bearing a tag are crucial tools for assessing protein location or function. Small tags such as Cys4 tag (tetracysteine; Cys-Cys-X-X-Cys-Cys) are less likely disrupt protein function in the living cell than green fluorescent protein. Herein we report the first example of the design and synthesis of a dual fluorescence and hyperpolarized (129)Xe NMR-based sensor of Cys4-tagged proteins. This sensor becomes fluorescent when bound to such Cys4-tagged peptides, and the (129)Xe NMR spectrum exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Most recently, Kotera et al attached hexa-carboxylate cryptophane to two arsenic moieties capable of interacting with proteins that contain a tetracysteine tag and observed a single peak that was shifted 6.4 ppm upon addition of excess Cys4-tagged peptide. 28 …”
Section: Cryptophane-based Xenon Biosensorsmentioning
confidence: 99%
“…Most recently, Kotera et al attached hexa-carboxylate cryptophane to two arsenic moieties capable of interacting with proteins that contain a tetracysteine tag and observed a single peak that was shifted 6.4 ppm upon addition of excess Cys4-tagged peptide. 28 …”
Section: Cryptophane-based Xenon Biosensorsmentioning
confidence: 99%
“…Here, however, the concept is extended to the conception and use of a probe that is activatable in both fluorescence and 129 Xe NMR spectroscopy (i.e., the responses of these modalities change upon binding to the target). With respect to our previous study, the reported chemical shift modifications of caged xenon induced by binding of the probe to the target should be improved further for in cellulo biosensing applications. In this study, a set of four biosensors and three targeted peptide motifs were investigated to optimize the 129 Xe NMR response.…”
Section: Introductionmentioning
confidence: 81%
“…In cases of smaller targeting units (like short peptides), a dye like Cy3 can be directly integrated into the cryptophane conjugate [ 228 ] to achieve the same goal. This strategy was also pursued for a folate sensor [ 176 ], generation of bimodal probes for detecting proteins that are genetically incorporated with a tetracysteine tag [ 229 , 230 ] and the sensor for enabling cell surface glycan detection [ 128 , 231 ]. These are examples for validating a targeted cellular uptake/binding of functionalized Xe hosts via fluorophore-based detection.…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%